2011
DOI: 10.3390/molecules16010624
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoids in Fruits of Different Persimmon Cultivars

Abstract: Carotenoids in the peel and the flesh of persimmon fruit were identified, and the contents of carotenoids in the fleshes of 46 different persimmon cultivars were analyzed. The results indicated that 31 specific carotenoids were detected in both cultivars of persimmons, among which nine specific carotenoids were characterized. β-Cryptoxanthin was the most abundant carotenoid among all individual components in both the peel and the flesh, accounting for about 20-30% of the total carotenoids in both cultivars. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 28 publications
(34 reference statements)
8
51
0
Order By: Relevance
“…While, Giordani et al (2011) reported that the contents of β-carotene in cultivars 'Fuji', 'Triumph' and 'Jiro' were 31, 45 and 93 μg/100 g, respectively, which were much lower than our results, probably due to cultivar differences and environmental effects. Zhou et al (2011) demonstrated that the content of β-carotene in cultivar 'YueShi' rapidly increased from green to mature, indicating that the maturity of persimmon fruit also had an important impact on the carotenoid content. The β-carotene content in persimmon was lower than that in mango, apricot and papaya, but higher than that in apple, pear and orange (Giordani et al 2011).…”
Section: β-Carotenementioning
confidence: 99%
See 1 more Smart Citation
“…While, Giordani et al (2011) reported that the contents of β-carotene in cultivars 'Fuji', 'Triumph' and 'Jiro' were 31, 45 and 93 μg/100 g, respectively, which were much lower than our results, probably due to cultivar differences and environmental effects. Zhou et al (2011) demonstrated that the content of β-carotene in cultivar 'YueShi' rapidly increased from green to mature, indicating that the maturity of persimmon fruit also had an important impact on the carotenoid content. The β-carotene content in persimmon was lower than that in mango, apricot and papaya, but higher than that in apple, pear and orange (Giordani et al 2011).…”
Section: β-Carotenementioning
confidence: 99%
“…yellow and orange to deep red, which results from the different contents of carotenoids (Zhou et al 2011). Persimmon fruits with high concentrations of carotenoids and polyphenols also exert greatly potential effects on preventing cardiovascular diseases (George and Redpath 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, they were higher, for example the β-cryptoxanthin on the Fuyu and Sheng varieties (RODRIGUEZ-AMAYA, 1997 exceptions, the reported values were higher in others research, for example the β-carotene on the Rama Forte variety (CARDOSO et al, 2011), the zeaxanthin and the β-cryptoxanthin in others cultivars (ZHOU et al, 2011), the α-carotene, the β-carotene and the cryptoxanthin on the Yotsumizo variety (RODRIGUEZ-AMAYA, 1997).…”
Section: Analysis Of Carotenoids and Vitamin Amentioning
confidence: 99%
“…al., 2011) (Table 2). However, others research showed that the β-carotene was the most abundant on the varieties Fuyu and Sheng (RODRIGUEZ-AMAYA, 1997, ZHOU et al, 2011. Table 2.…”
Section: Analysis Of Carotenoids and Vitamin Amentioning
confidence: 99%
See 1 more Smart Citation